Cultura y comunicación: nuevas emocionalidades, nuevos mundos - Barboza Tello, Marco (2017)
From contemporary social characterizations made by Umberto Eco and ZygmuntBauman, the categories of handicraftsman-artist and of passions against passions are developed to explain the characteristics of the present world, where technology, emotionality, reflexive homesickness, and revaluing cultured production among themselves are central themes from a socio-cultural perspective of communication.